2003
DOI: 10.1016/s0168-6496(03)00033-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide conversion by anaerobic bioreactor sludges

Abstract: Seven different anaerobic sludges from wastewater treatment reactors were screened for their ability to convert carbon monoxide (CO) at 30 and 55 degrees C. At 30 degrees C, CO was converted to methane and/or acetate by all tested sludges. Inhibition experiments, using 2-bromoethanesulfonic acid and vancomycine, showed that CO conversion to methane at 30 degrees C occurred via acetate, but not via H2. At 55 degrees C, four sludges originally cultivated at 30-35 degrees C and one sludge cultivated at 55 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
54
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 21 publications
(31 reference statements)
10
54
1
Order By: Relevance
“…The neutrophilic sludges were obtained from anaerobic bioreactors for biological sulfate reduction to produce sulfide for metal removal. One sludge originated from a chemical plant in Emmen, The Netherlands (Dar et al, 2007) and the other sludge from a zinc smelter in Budel, The Netherlands (Sipma et al, 2003). These sludges were termed Paques sludge and Budel sludge, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The neutrophilic sludges were obtained from anaerobic bioreactors for biological sulfate reduction to produce sulfide for metal removal. One sludge originated from a chemical plant in Emmen, The Netherlands (Dar et al, 2007) and the other sludge from a zinc smelter in Budel, The Netherlands (Sipma et al, 2003). These sludges were termed Paques sludge and Budel sludge, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Carboxydotrophic bacteria can use CO as their only carbon source [2][3][4], at low temperatures and pressures. Their ability to oxidize and metabolize CO is connected to the existence of the enzyme CO-dehydrogenase [3], often found in carboxydotrophic methanogens and acetogens [5], resulting pre-dominantly in methane and acetate production, respectively. Metabolic activity of carboxydotrophic mesophilic bacteria also results in the formation of H 2 , ethanol, butyrate, butanol, and acetate [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The authors speculated that a main part of the CO was converted by homoacetogens, preventing CO toxicity for SO 4 -reducing bacteria. Several anaerobic bioreactor sludges at 55°C were able to convert 100% CO in SO 4 -free media to H 2 or to methane via H 2 as intermediate (Sipma et al 2003). Recently, it was demonstrated that in anaerobic bioreactor sludges, both CO and H 2 were used by SO 4 -reducing bacteria that tolerated and used high CO (P co >1.6 bar) concentrations (Sipma et al 2004).…”
Section: Introductionmentioning
confidence: 99%